Towards Quality and Sustainable Tourism in Bali: Should the Regional Master Plan be Adjusted? - Palguna, I Dewa Gede; Hadi Santosa, Anak Agung Gede Duwira; Yasa, Made Maharta; Pramana, I Gede Pasek (Udayana Journal of Law and Culture, 2023)
Bali is the area in Indonesia that is most affected economically due to the paralysis of the tourism industry during the Covid-19 Pandemic. Consequently, tourism development programs designed by the government faced many obstacles in their implementation. This article discusses how the concept of quality and sustainable tourism are incorporated into the Tourism Master Plan of the Bali Province 2015-2029. Further, it evaluates the implementation of the master plan during the Covid-19 Pandemic. This writing is designed based on legal research that applies a policy-oriented approach. The research collected and analyzed primary sources in the form of law, regulation, and policy at the national and regional levels, as well as secondary sources that are available in textbooks, journal articles, and website content. A series of qualitative interviews and a focus group discussion were conducted to deepen understanding of legal and non-legal matters. This article suggested that even though the concept of quality and sustainable tourism has been incorporated into the aforementioned master plan, the document implies a contradiction between the vision that desires to apply the concept and the goals and objectives which tend to support quantity tourism. The qualitative evaluation indicated that the master plan could not be appropriately implemented and requires an adjustment to bring in again the vision into the implementing policy adopted by the provincial government.